Short-term fitness and long-term population trends in the orchid Anacamptis morio - Hornemann, Gitte; Michalski, Stefan G.; Durka, Walter (Plant ecology, 2012)
The conservation of endangered species critically depends on the understanding to which degree short-term fitness and long-term trends are affected by intrinsic local conditions and external global dynamics. However, studies combining longterm demographic data with population level analyses of site conditions, genetic variation, and reproduction as well as with climatic data are still rare. Here we studied the endangered orchid Anacamptis mono, representative for species with a sub-mediterranean distribution. For populations at the northern range edge, we combined long-term monitoring data (1977-2010) with climatic data and analyzed reproductive fitness components, genetic variation, and abiotic site conditions. Reproduction was generally low as expected from the deceptive pollination system, and was positively influenced by population size and xerothermic site quality. The majority of populations showed a positive population trend, which was paralleled by an increase in spring temperature and positively affected by site quality. High levels of genetic variation were found in the populations which were at gene flow-drift equilibrium. A. morio may profit from increasing spring temperatures because of increased reproductive output. Nevertheless, whether climate change results in fitness increase or not may depend on the maintenance and provision of optimal site quality, i.e., xerothermic and nutrient poor conditions.